2013
DOI: 10.1590/s0100-736x2013001300009
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological characteristics of teeth in agouti (Dasyprocta prymnolopha Wagler, 1831)

Abstract: Pesq. Vet. Bras. 33(Supl.1):51-57, dezembro 2013 51 RESUMO.-[Características anatômicas e histológicas dos dentes na cutia (Dasyprocta prymnolopha Wagler, 1831).] A cutia espécie Dasyprocta prymnolopha (D. prymnolopha) é um roedor de tamanho médio, diurno e característico do Nordeste do Brasil, sul da Amazônia. Vários estudos têm sido feitos sobre estes roedores. No entanto, há uma carência de estudos do sistema estomatognático, em particular, a morfologia dos dentes. Assim, esta pesquisa procura descrever asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…An examination of the specimens showed that both juveniles had suffered bites to the throat resulting in deep puncture wounds, in addition to severe wounds to the abdomen that had exposed internal organs. The wounds were consistent with those likely to be caused by the dentition of adults of the species (da Silva et al, ). As two of the adult agoutis had remained nearby during examination of the bodies, the observers retreated to cover to make further observations.…”
Section: Observation Of Infanticide and Cannibalismsupporting
confidence: 78%
“…An examination of the specimens showed that both juveniles had suffered bites to the throat resulting in deep puncture wounds, in addition to severe wounds to the abdomen that had exposed internal organs. The wounds were consistent with those likely to be caused by the dentition of adults of the species (da Silva et al, ). As two of the adult agoutis had remained nearby during examination of the bodies, the observers retreated to cover to make further observations.…”
Section: Observation Of Infanticide and Cannibalismsupporting
confidence: 78%
“…The Dasyprocta leporine (Lichtenstein, 1823 ) , commonly named red‐rumped agouti, is one of the 11 agoutis species, a group of rodents found predominantly in Latin America (Emmons & Reid, ). This species presents an important role in the food chain, such as being involved in the spread of many plant species (Silva et al, ). Due to interest in its meat and the destruction of its habitat, its population has been reduced over the years (Hosken & Silveira, ), even if D. leporine remains globally considered as a least concern species (Emmons & Reid, ).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Queiroz & Kipnis (1990), essa coleção osteológica corresponde às atividades de caça realizadas imediatamente após a mudança para a reserva indígena Caru, no ano de 1987. Para a análise da parte de diversidade observada, fizeram-se comparações com a coleção osteológica de referência do Laboratório de Estudos Evolutivos Humanos, consulta aos trabalhos de Bonvicino et al (2008) e Silva et al (2013) e, no tocante à tafonomia, foram utilizadas técnicas desenvolvidas por Behrensmeyer (1991), para a análise de concentrações e assembleias ósseas.…”
Section: Methodsunclassified
“…O crânio mostrado na figura 2 é similar ao de indivíduos adultos da espécie Dasyprocta prymnolopha Wagler, 1831(SILVA et al, 2013, porém o tamanho e o formato geral são indistinguíveis dos de outras espécies do gênero Dasyprocta e por isso se optou pela identificação Dasyprocta sp. (cutia).…”
Section: Família Dasyproctidaeunclassified